2021
DOI: 10.3390/horticulturae7040075
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Immature and Mature Pepper (Capsicum annuum L.) Seeds in Relation to Bio-Priming with Endophytic Pseudomonas and Bacillus spp.

Abstract: Fruit maturity for seed production can occur at various times because of the continual flowering of pepper plants. Accordingly, seeds with different maturity are acquired as the fruits are collected in a single harvest. Immature seeds obtained in this harvest may lead to a decrease in the quality of seed lots. Therefore, this research aimed to evaluate the influence of four different endophytic bacteria strains (Pseudomonas fluorescens strain L5b, Pseudomonas gessardii strain L13, Bacillus subtilis strain Bs1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Bolaños et al 30 reported a 23.61% higher germination in chili pepper seeds (C. annuum L.) inoculated with B. licheniformis M2-7. In another study, B. subtilis increased the germination of "Kandil Dolma" peppers by 14.68% 31 . The increases can be attributed to the production of bacterial-origin growth regulators, such as gibberellins, cytokinins, and auxins, as there is a direct relationship between the concentration of phytohormones and the physiological state of the chiltepin seed 32 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bolaños et al 30 reported a 23.61% higher germination in chili pepper seeds (C. annuum L.) inoculated with B. licheniformis M2-7. In another study, B. subtilis increased the germination of "Kandil Dolma" peppers by 14.68% 31 . The increases can be attributed to the production of bacterial-origin growth regulators, such as gibberellins, cytokinins, and auxins, as there is a direct relationship between the concentration of phytohormones and the physiological state of the chiltepin seed 32 .…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, the production of exogenous auxins 31 , allows early root development 32 , through cell division and wall extensibility by enzymatic action 35 . In this study, chiltepin seeds had an overall germination time of 7.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial communities associated with tomato seeds have been more extensively studied than the corresponding communities associated with pepper seeds: most published research focuses on beneficial endophytes as a significant portion of the total seed microbiome [24,25].…”
Section: Seed Endophytes: Recruitment and Rolementioning
confidence: 99%
“…The microbial communities associated to tomato seeds have been more extensively studies than the corresponding communities associated to pepper seeds: most published research is focusing on beneficial endophytes as a significant portion of the total seed microbiome [25][26][27][28][29].…”
Section: Seed Endophytes: Recruitment and Dynamicsmentioning
confidence: 99%